Low-birefringence and high-heat-resistance cycloolefin polymer and preparation method thereof
By introducing a symmetric alicyclic structure into the cycloolefin polymer, the birefringence and the heat resistance are improved, the problem of image distortion and insufficient heat resistance caused by the birefringence effect in optical lenses in the prior art is solved, and the problem of image distortion and insufficient heat resistance is achieved. High-quality imaging effects and material properties.
Patent Information
- Application Number
- CN202411080698.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-08
AI Technical Summary
The existing cycloolefin polymers have problems with image distortion and dizziness caused by birefringence effects in large-size optical lenses, and their heat resistance is insufficient, which affects the imaging quality.
Using low birefringence, high heat-resistant cycloolefin polymers, which contain specific structural units prepared by two-step process of ring opening polymerization and hydrogenation, the symmetrical alicyclic structure is introduced to balance the intermolecular forces, reduce the birefringence and increase the Heat resistance while maintaining high refractive index and low hygroscopicity.
It effectively reduces the birefringence of the material, improves heat resistance and refractive index, combines high ABB number and low hygroscopicity, improves the imaging quality of the optical lens and reduces eye fatigue during use.
Smart Images

Figure BDA0004983646630000021 
Figure BDA0004983646630000022 
Figure BDA0004983646630000023
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyolefins, and in particular to a low-birefringence, high-heat-resistant cycloolefin polymer and a preparation method thereof. Background Art
[0002] In recent years, as the manufacturing technology of optoelectronic devices has developed rapidly, the requirements for optical lenses have gradually increased. The birefringence of a lens is the phenomenon that when light passes through a lens, the refracted light is split into two beams due to different incident angles or polarization states, resulting in different refractive indices for the two beams. Reducing the birefringence of a lens can significantly reduce image distortion, deformation or ghosting caused by the birefringence effect, thereby greatly improving the image quality.
[0003] Cycloolefin polymer is an amorphous, transparent polymer with a highly hindered cyclic alkane structure on the main chain of the molecule. Japan Zeon Co., Ltd. and Japan Synthetic Rubber Co., Ltd. prepared the corresponding commercial products ZEONEX, ZEONOR, and ARTON by ring-opening metathesis polymerization of cycloolefins and hydrogenation of unsaturated bonds. Due to its excellent properties of good light transmittance, high refractive index, high Abbe number, low birefringence and good molding processability, cycloolefin polymer is widely used as optical components for mobile phones, car-mounted, and security lenses.
[0004] Although cycloolefin polymers have become an ideal material for small-sized optical lenses, their molecular chain structure still lacks symmetry and cannot balance the intermolecular forces in the lateral and longitudinal directions, making it impossible to achieve "zero birefringence". When used as large-sized optical lenses such as AR / VR, there is still a certain degree of optical distortion during imaging, and there are still drawbacks of dizziness and eye fatigue after long-term use. Summary of the invention
[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a low birefringence, high heat resistance cycloolefin polymer and a preparation method thereof. The low birefringence, high heat resistance cycloolefin polymer of the present invention reduces birefringence and improves heat resistance, while also improving the refractive index of the material to a certain extent and having the characteristics of high Abbe number and low hygroscopicity.
[0006] In order to achieve the above technical effects, the present invention adopts the following scheme:
[0007] The present invention provides a low birefringence, high heat resistance cycloolefin polymer, which comprises a structural unit as shown in the following formula I:
[0008]
[0009] In formula I, R is a cycloalkyl group, preferably one or more selected from cyclopentanyl, cyclohexanyl, cycloheptyl, cyclooctyl, norbornyl, adamantyl, etc. and their substituted structures; R1, R2, R3, and R4 are independently selected from one or more selected from H, methyl, ethyl, butyl, hexyl, cyclohexyl, phenyl, etc.; R1 and R4 are bonded to each other to form a ring or are not bonded; L is -CH2-CH2- or -CH=CH-; and n is an integer from 0 to 2.
[0010] In some preferred embodiments, the low birefringence and high heat resistance cycloolefin polymer of the present invention further comprises a structural unit as shown in the following formula II:
[0011]
[0012] In Formula II, RC is any one of an alkyl group and a cycloalkyl group, preferably a C4-C8 alkyl group, a C5-C 15 Any of the cycloalkyl groups of C4-C8, more preferably C4-C8 alkylene groups, C5-C 15 Any one of the groups containing a cyclopentane structure.
[0013] In some specific embodiments, the low birefringence, high heat-resistant cycloolefin polymer of the present invention, based on the total molar amount of the structural units represented by formula I and the structural units represented by formula II as 100%, the molar content of the structural units represented by formula I is 5-100 mol%, for example, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 mol%, and the molar content of the structural units represented by formula II is 0-95 mol%, for example, 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 95 mol%.
[0014] In some preferred embodiments, the structural unit represented by formula I of the present invention is prepared by ring-opening polymerization of the compound represented by formula I-A under the action of a chain transfer agent:
[0015]
[0016] In Formula Ⅰ-A, R1, R2, R3, R4, n, and R are defined the same as R1, R2, R3, R4, n, and R in Formula Ⅰ above;
[0017] Preferably, the compound represented by formula Ⅰ-A is selected from at least one of compounds M-1, M-2, M-3, M-4, M-5, M-6, and M-7 having the following structures:
[0018]
[0019] In some preferred embodiments, the structural unit represented by formula II of the present invention is prepared by a cycloolefin compound represented by formula II-A:
[0020]
[0021] Wherein, the definition of RC is the same as that of RC in the above formula II;
[0022] Preferably, the cycloolefin compound represented by formula II-A is at least one selected from cyclopentene, cyclohexene, cycloheptene, cyclooctene, cyclooctadiene, norbornene, dicyclopentadiene and tetracyclododecene.
[0023] In the present invention, the low birefringence and high heat-resistant cycloolefin polymer has a number average molecular weight of 5000-100000, for example, 5000, 10000, 20000, 30000, 40000, 50000, 60000, 70000, 80000, 90000, 100000.
[0024] In the present invention, the low birefringence, high heat resistance cycloolefin polymer has a double bond molar content of ≤50%, such as 50, 45, 40, 35, 30, 25, 20, 15, 10, 5, 1%, preferably ≤1%.
[0025] In the present invention, the low birefringence and high heat-resistant cycloolefin polymer has a glass transition temperature (Tg) of 120-180°C, a stress birefringence (CR) of 1-5nm, a refractive index (nd) of 1.53-1.60, an Abbe number (νd) of 50-60, and a moisture absorption rate of ≤0.1%.
[0026] The present invention also provides a method for preparing the above-mentioned low birefringence and high heat-resistant cycloolefin polymer. The method for preparing the olefin polymer is well known to those skilled in the art. The following is only an exemplary description and does not constitute any limitation.
[0027] For example, a method for preparing a low birefringence, high heat resistance cycloolefin polymer is obtained through two steps of step (1) polymerization and step (2) hydrogenation. Taking the structural unit shown in formula I as an example, the reaction route is shown as follows:
[0028]
[0029] Specifically, a method for preparing the above-mentioned low birefringence and high heat-resistant cycloolefin polymer comprises the following steps:
[0030] (1) Polymerization: mixing a compound represented by formula Ⅰ-A, an optional cycloolefin compound represented by formula Ⅱ-A, and a chain transfer agent to carry out a polymerization reaction to obtain a polymer intermediate solution;
[0031] (2) Hydrogenation: The polymer intermediate solution obtained in step (1) is subjected to a hydrogenation reaction with hydrogen to obtain the cycloolefin polymer.
[0032] In the present invention, the polymerization process of step (1) is specifically as follows: adding the compound represented by formula Ⅰ-A, the optional cycloolefin compound represented by formula Ⅱ-A, a chain transfer agent, and a ring-opening metathesis polymerization catalyst into a solvent to carry out a solution polymerization reaction.
[0033] Among them, the molar ratio of the compound represented by formula Ⅰ-A to the optional cycloolefin compound represented by formula Ⅱ-A is (5-100):(95-0), for example (5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100):(95, 90, 80, 70, 60, 50, 40, 30, 20, 10, 0).
[0034] The chain transfer agent is selected from at least one of terminal double bond-containing olefin compounds, preferably at least one of 1-pentene, 1-hexene, 1-heptene, 1-octene, styrene, vinyl ether, etc.;
[0035] Preferably, the molar ratio of the chain transfer agent to the sum of the compound represented by formula Ⅰ-A and the optional cycloolefin compound represented by formula Ⅱ-A is 1:(50-2000), for example 1:50, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000, 1:2000.
[0036] Among them, there are many types of ring-opening metathesis polymerization catalysts, and conventional selections in the field can be used. The present invention has no special requirements for them. For example, it can be any one or a combination of at least two of a multi-component tungsten catalyst, a Grubbs series catalyst, and a Schrock series catalyst, preferably a Grubbs series catalyst;
[0037] Preferably, the mass ratio of the ring-opening metathesis polymerization catalyst to the sum of the compound represented by formula Ⅰ-A and the optional cycloolefin compound represented by formula Ⅱ-A is 1:10000-1000000, for example, 1:10000, 1:50000, 1:100000, 1:300000, 1:500000, 1:700000, 1:1000000.
[0038] Wherein, the solvent is selected from at least one of aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, halogenated aromatic hydrocarbon solvents, and ether solvents;
[0039] Preferably, the aliphatic hydrocarbon solvent is selected from at least one of n-hexane and heptane;
[0040] Preferably, the alicyclic hydrocarbon solvent is selected from at least one of cyclopentane, cyclohexane, methylcyclohexane and dimethylcyclohexane;
[0041] Preferably, the aromatic hydrocarbon solvent is selected from at least one of benzene, toluene and xylene;
[0042] Preferably, the halogenated aromatic hydrocarbon solvent is selected from at least one of chlorobenzene and dichlorobenzene;
[0043] Preferably, the ether solvent is selected from at least one of diethyl ether and tetrahydrofuran;
[0044] Preferably, the total mass of the compound represented by formula Ⅰ-A and the optional cycloolefin compound represented by formula Ⅱ-A accounts for 5 to 70% of the mass of the solvent, such as 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70%, preferably 5 to 50%;
[0045] Wherein, the solution polymerization reaction has a temperature of 0 to 200°C, such as 0, 10, 30, 50, 80, 100, 130, 150, 180, 200°C, preferably 50 to 150°C; and a time of 1 to 60 min, such as 1, 10, 20, 30, 40, 50, 60 min, preferably 1 to 30 min.
[0046] In the present invention, the hydrogenation process of step (2) is specifically as follows: the polymer intermediate solution obtained in step (1) is subjected to a hydrogenation reaction with hydrogen in the presence of a hydrogenation catalyst.
[0047] Wherein, the hydrogenation catalyst includes a homogeneous or heterogeneous catalyst, which can be selected conventionally in the field, and the present invention has no special requirements for it;
[0048] Preferably, the heterogeneous catalyst is selected from at least one of metal-supported silica, metal-supported alumina, metal-supported titanium oxide, skeleton nickel, palladium-carbon catalyst, etc.; wherein the metal is selected from at least one of nickel, palladium, platinum, rhodium, and ruthenium;
[0049] Preferably, the amount of the heterogeneous catalyst added is 0.5-10% of the mass of the polymer intermediate solution obtained in step (1), for example, 0.5, 1, 3, 5, 7, 9, 10%;
[0050] Preferably, the homogeneous catalyst is selected from at least one of soluble complexes of metals such as nickel, titanium, palladium, platinum, rhodium, ruthenium, etc., such as a Ziegler hydrogenation catalyst composed of nickel salt-alkyl aluminum, a titanocene-alkyl lithium hydrogenation catalyst, a Ru(X)Cl(CO)L2 type complex catalyst, etc.;
[0051] Preferably, the amount of the homogeneous catalyst added is 0.001-10% of the mass of the polymer intermediate solution obtained in step (1), for example, 0.001, 0.01, 0.1, 0.5, 1, 3, 5, 7, 9, 10%.
[0052] Wherein, the hydrogenation reaction is carried out under high temperature and high pressure;
[0053] The hydrogenation temperature is 80 to 200°C, for example, 80, 100, 130, 150, 180, 200°C;
[0054] The amount of hydrogen fed is determined by the charging pressure, and the charging pressure of hydrogen is controlled to be 1-7MPa of the reaction pressure, for example, 1, 2, 3, 4, 5, 6, 7MPa;
[0055] Preferably, the hydrogenation reaction ends when the molar content of double bonds in the obtained low birefringence, high heat-resistant cycloolefin polymer is ≤50%, for example, 50, 45, 40, 35, 30, 25, 20, 15, 10, 5, 1%, preferably ≤1%.
[0056] Preferably, step (1) in the present invention further includes terminating the reaction, and step (2) further includes post-treatment processes such as acidification, flocculation, washing, and drying, all of which are conventional operations in the art and are not specifically limited in the present invention.
[0057] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0058] The low birefringence and high heat-resistant cycloolefin polymer of the present invention introduces a symmetrical alicyclic structure, improves the symmetry of the molecular chain to balance and offset the intermolecular forces of the material in the transverse and longitudinal directions, and further reduces the birefringence of the material. The symmetrical rigid alicyclic structure can further improve the heat resistance and refractive index of the material. At the same time, the present invention does not introduce additional unsaturated bonds and polar groups, and can maintain the characteristics of high Abbe number and low hygroscopicity of the material. DETAILED DESCRIPTION
[0059] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the following specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0060] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0061] The raw materials used in the examples are all conventional raw materials in the art, and the purity specifications used are analytically pure or chemically pure.
[0062] The sources of the raw materials used in the following examples are as follows. Unless otherwise specified, all other raw materials are conventional raw materials in the art, and the purity specifications used are analytically pure or chemically pure:
[0063] High-purity hydrogen: 99.999%, Dalian Guangming Special Gas Co., Ltd.;
[0064] Dicyclopentadiene: 98% (GC), Sigma-Aldrich;
[0065] Cyclooctene: 95% (GC), J&K Technologies;
[0066] 1-Hexene: 99%, Sigma-Aldrich;
[0067] 1-Octene: 99%, J&K Technology;
[0068] Cyclopentadienyl lithium: 97%, Shanghai MacLean Biochemical Technology Co., Ltd.;
[0069] Norbornene: 98%, TCI;
[0070] Tetracyclododecene: 98%, TCI;
[0071] Chloroadamantane: 98%, Shanghai Aladdin;
[0072] Chlorocyclopentane: 98%, Shanghai Aladdin;
[0073] Chlorocyclohexane: 99%, Shanghai Aladdin;
[0074] Cyclohexene: 98%, Shanghai Aladdin;
[0075] Vinyl cyclohexane: 98%, Shanghai Aladdin; Grubbs 2nd generation catalyst: 99.95%, Shanghai Aladdin;
[0076] Supported nickel catalyst: Ni@Al2O3, Alfa;
[0077] Nickel acetylacetonate: 95%, Shanghai Aladdin;
[0078] Triisobutylaluminum: 1.0 M n-hexane solution, Aladdin, Shanghai.
[0079] The performance test parameters and corresponding test methods used in various embodiments of the present invention are as follows:
[0080] The structures of the compounds and polymers synthesized in the present invention were measured by a Bruker ARX-400 nuclear magnetic resonance spectrometer using deuterated chloroform (CDCl3), deuterated benzene (C6D6), and deuterated 1,1,2,2-tetrachloroethane (C2D2Cl4) as solvents at room temperature or 90°C.
[0081] The molecular weight and molecular weight distribution of the polymer synthesized in the present invention are obtained by testing at 150° C. using PL-GPC220, using three PLgel 10 μm MIXED-B separation columns connected in series and 1,2,4-trichlorobenzene as the solvent.
[0082] The thermal properties (glass transition temperature Tg) of the polymers were measured using a TA Q2000 differential scanning calorimeter in accordance with ISO 11357.
[0083] The refractive index (nd) and Abbe number (vd) of the polymer were measured by Atago DR-M4 refractometer according to ASTM-D542 standard; the birefringence (CR) of the polymer was measured by Pla WPA-200. The heat deformation temperature (HDT) of the polymer was measured according to ASTM D648 standard.
[0084] The water absorption rate of the polymer is determined by a swelling method. The prepared sample is dried, immersed in water at 25°C for 48 hours, then taken out and weighed, and the percentage of weight increase is calculated.
[0085] Specific embodiments
[0087] (I) Monomer preparation:
[0088] Synthesis example-1
[0089]
[0090] In a glove box, add 2.1 mol of cyclopentadienyl lithium and 1000 ml of n-hexane to a 2L flask. After uniform dispersion, take 2.1 mol of chlorocyclopentane and drop it into the flask. After the addition is completed, continue stirring for 30 minutes, filter and separate, and drain the filtrate to obtain cyclopentylcyclopentadiene. 1H NMR (400MHz, CDCl3): δ=6.21(2H), δ=6.08(2H), δ=2.86(1H), δ=1.94–1.87(4H); δ=1.58(3H); δ=1.11(2H).
[0091] Synthesis example-2
[0092]
[0093] The preparation of cyclohexanecyclopentadiene is the same as that of cyclopentylcyclopentadiene, except that chlorocyclohexane is used instead of chlorocyclopentane. 1H NMR (400MHz, CDCl3): δ=6.21(2H), δ=6.08(2H), δ=2.89(1H), δ=1.95(1H); δ=1.78(1H); δ=1.53(2H); δ=1.30-1.23(5H); δ=1.19(1H).
[0094] Synthesis example-3
[0095]
[0096] The preparation of adamantylcyclopentadiene is the same as that of cyclopentylcyclopentadiene, except that chloroadamantane is used instead of chlorocyclopentane. 1H NMR (400MHz, CDCl3): δ=6.20 (2H), δ=6.06 (2H), δ=2.80 (1H), δ=2.01-1.95 (3H); δ=1.80-1.76 (3H); δ=1.58 (2H); δ=1.46 (1H); δ=1.38-1.39 (3H); δ=1.01-1.23 (3H).
[0097] Monomer Synthesis Example-1
[0098]
[0099] In a 2L stainless steel autoclave, 1.9 mol of cyclopentylcyclopentadiene was added, the atmosphere in the autoclave was replaced with nitrogen and then replaced with ethylene, the ethylene pressure was increased to 3MPa, stirring was started, the autoclave was heated to 180°C and the ethylene pressure was increased to 5MPa, and the reaction was continued for 6h. After the reaction, the autoclave was cooled to room temperature, and the reactants were purified by column chromatography (ethyl acetate / petroleum ether=1 / 10) to obtain the corresponding monomer. 1H NMR (400MHz, CDCl3): δ=5.83 (2H), δ=2.66 (2H), δ=1.94-1.82 (6H), δ=1.57–1.54 (4H); δ=1.35 (2H); δ=1.08 (2H).
[0100] Monomer Synthesis Example-2
[0101]
[0102] The preparation of monomer M-2 is the same as that of monomer M-1, except that cyclohexylcyclopentadiene replaces cyclopentylcyclopentadiene. 1H NMR (400 MHz, CDCl3): δ = 5.83 (2H), δ = 2.66 (2H), δ = 2.34 (1H), δ = 1.85-1.78 (2H); δ = 1.57-1.50 (4H); δ = 1.35-1.23 (7H); δ = 1.17 (2H).
[0103] Monomer Synthesis Example-3
[0104]
[0105] The preparation of monomer M-3 is consistent with that of monomer M-1, except that adamantyl cyclopentadiene replaces cyclopentyl cyclopentadiene. 1H NMR (400 MHz, CDCl3): δ = 5.86 (2H), δ = 2.78-2.75 (2H), δ = 2.01-1.94 (3H), δ = 1.80-1.74 (3H); δ = 1.58-1.55 (4H); δ = 1.44 (2H); δ = 1.37-1.36 (5H); δ = 1.29-0.83 (5H).
[0106] Monomer Synthesis Example-4
[0107]
[0108] In a 2L stainless steel autoclave, 1.9 mol of cyclohexylcyclopentadiene and 3.5 mol of vinylcyclohexane were added, the atmosphere in the autoclave was replaced with nitrogen, stirring was started, and the reaction was heated to 180°C for 6 hours. After the reaction was completed, the autoclave was cooled to room temperature, and the reactants were purified by column chromatography (ethyl acetate / petroleum ether=1 / 10) to obtain the corresponding monomer.
[0109] 1H NMR (400MHz, CDCl3): δ=5.43(2H), δ=2.36(1H), δ=2.02-1.97(1H), δ=1.68-1.12(26H).
[0110] Monomer Synthesis Example-5
[0111]
[0112] The synthesis is consistent with M-4, except that cyclohexene is used instead of vinylcyclohexane. 1H NMR (400MHz, CDCl3): δ = 5.43 (2H), δ = 2.36-2.30 (3H), δ = 2.02 (2H), δ = 1.78-1.71 (2H); δ = 1.50 (4H); δ = 1.34-1.23 (7H); δ = 1.17-1.02 (6H).
[0113] Monomer Synthesis Example-6
[0114]
[0115] The synthesis is consistent with that of M-4, except that adamantylcyclopentadiene is used to replace cyclohexylcyclopentadiene, and cyclohexene is used to replace vinylcyclohexane. 1H NMR (400MHz, CDCl3): δ=5.43 (2H), δ=2.44-2.41 (2H), δ=2.03-1.94 (5H), δ=1.80-1.74 (3H); δ=1.56-1.53 (5H); δ=1.44 -1.23 (8H); δ=1.09-0.83 (7H).
[0116] Monomer Synthesis Example-7
[0117]
[0118] The synthesis is consistent with that of M-6, except that cyclohexene is replaced by norbornene. 1H NMR (400 MHz, CDCl3): δ = 5.50 (2H), δ = 2.50-2.47 (2H), δ = 2.05-1.71 (10H), δ = 1.61-1.46 (3H); δ = 1.44-0.77 (15H).
[0119] (II) Polymer preparation
[0120] Example 1
[0121] HPM-1 preparation
[0122]
[0123] (1-1) Preparation of Ring-Opening Polymer (PM-1)
[0124] In a glove box, take 2.12g of dicyclopentadiene, 6.42g of tetracyclododecene, and 3.90g of monomer M-1, dissolve them in 44g of xylene, and then add 50.2mg of 1-hexene. Add the above solution to a 250ml flask equipped with a magnetic, start stirring and heating; when the temperature rises to 40°C, add 0.3mg of Grubbs second-generation catalyst to the flask to start polymerization. After 30min of polymerization, add 1g of ethanol to terminate the active center. The total amount of the reaction solution is 50g. The weight average molecular weight Mw of the obtained ring-opening polymer is 1.3×10 4 , the conversion rate of monomer to polymer is >99%.
[0125] (1-2) Hydrogenation of Ring-Opening Polymer (HPM-1)
[0126] In a glove box, 25.8 mg (100 μmol) of nickel acetylacetonate was weighed and dispersed in 5 g of xylene. 0.4 g (0.5 mmol) of triisobutylaluminum was extracted and injected into the nickel acetylacetonate. The mixture was reacted for 2 min to prepare a hydrogenation catalyst.
[0127] Weigh 40g of the ring-opening polymer reaction liquid in (1-1), add 40g of xylene to dilute it, and transfer it to a stainless steel reactor that has been dried in advance, and replace the atmosphere in the reactor with nitrogen and hydrogen three times in sequence. Inject 3g of the above-prepared hydrogenation catalyst into the reactor, pressurize it to 4MPa with hydrogen, start stirring and heat to 80°C. After 4 hours of reaction, the double bond content in the product is reduced to 1%, which is the end point of the hydrogenation reaction. The corresponding hydrogenated polymer solution is obtained. After cooling, centrifugation is performed, and the supernatant is poured into acidified ethanol, flocculated and washed three times, and the precipitated polymer is washed three times with deionized water and dried in a vacuum oven. The obtained hydrogenated polymer, i.e., polymer (HPM-1), has a weight-average molecular weight Mw of 1.5×10 4 , the residual double bond content is <1%.
[0128] (1-3) Preparation of hydrogenated polymer membrane
[0129] Take 2 g of the cycloolefin polymer obtained in step (1-2) and add 10 ml of xylene to dissolve it. Pour the dissolved polymer solution into a clean mold and evaporate the solvent to obtain the corresponding polymer film.
[0130] The glass transition temperature (Tg), stress birefringence (CR), refractive index (nd) and Abbe number (νd) of the cycloolefin polymer HPM-1 obtained by the above-mentioned test method are shown in Table 1.
[0131] Example 2
[0132] HPM-2 preparation
[0133]
[0134] (2-1) Preparation of Ring-Opening Polymer (PM-2)
[0135] In a glove box, take 0.79g of dicyclopentadiene, 3.53g of tetracyclododecene, and 2.12g of monomer M-2, dissolve them in 44g of cyclohexane, and then add 26.8mg of 1-hexene. Add the above solution to a 250ml flask equipped with a magnetic, start stirring and heating; when the temperature rises to 40°C, add 0.3mg of Grubbs second-generation catalyst to the flask to start polymerization. After 30min of polymerization, add 1g of ethanol to terminate the active center. The total amount of the reaction solution is 50g. The weight average molecular weight Mw of the obtained ring-opening polymer is 2.7×10 4, the conversion rate of monomer to polymer is >99%.
[0136] (2-2) Hydrogenation of Ring-Opening Polymer (HPM-2)
[0137] Weigh 40g of the ring-opening polymer reaction liquid in (2-1) and transfer it to a stainless steel reactor that has been dried in advance. Add 2g of loaded nickel catalyst to the reactor. After sealing the reactor, replace the atmosphere in the reactor with nitrogen and hydrogen three times in sequence. Pressurize it to 4MPa with hydrogen, start stirring and heat to 130°C. After 4 hours of reaction, the double bond content in the product is reduced to 1%, which is the end point of the hydrogenation reaction. The corresponding hydrogenated polymer solution is obtained. After cooling, centrifugation is performed, and the supernatant is poured into acidified ethanol, flocculated and washed three times, and the precipitated polymer is washed three times with deionized water and dried in a vacuum oven. The obtained hydrogenated polymer, i.e., polymer (HPM-2), has a weight-average molecular weight Mw of 2.8×10 4 , the residual double bonds are less than 1%.
[0138] (2-3) Preparation of hydrogenated polymer membrane
[0139] Take 2 g of the hydrogenated polymer obtained in step (2-2) and add 10 ml of xylene to dissolve it. Pour the dissolved polymer solution into a clean mold and evaporate the solvent to obtain the corresponding hydrogenated polymer film.
[0140] The glass transition temperature (Tg), stress birefringence (CR), refractive index (nd) and Abbe number (νd) of the hydrogenated polymer HPM-2 obtained by the above method are shown in Table 1.
[0141] Example 3
[0142] HPM-3 preparation
[0143]
[0144] (3-1) Preparation of Ring-Opening Polymer (PM-3)
[0145] In a glove box, take 2.16g of dicyclopentadiene, 2.56g of tetracyclododecene, and 1.83g of monomer M-3, dissolve them in 33g of xylene, and then add 67.2mg of 1-hexene. Add the above solution to a 250ml flask equipped with a magnetic, start stirring and heating; when the temperature rises to 40°C, add 0.3mg of Grubbs second-generation catalyst to the flask to start polymerization. After 30min of polymerization, add 1g of ethanol to terminate the active center. The total amount of the reaction solution is 40g. The weight average molecular weight Mw of the obtained ring-opening polymer is 1.1×10 4 , the conversion rate of monomer to polymer is >99%.
[0146] (3-2) Hydrogenation of Ring-Opening Polymer (HPM-3)
[0147] In a glove box, 25.8 mg (100 μmol) of nickel acetylacetonate was weighed and dispersed in 5 g of xylene. 0.4 g (0.5 mmol) of triisobutylaluminum was extracted and injected into the nickel acetylacetonate. The mixture was reacted for 2 min to prepare a hydrogenation catalyst.
[0148] Weigh 30g of the ring-opening polymer reaction liquid in (3-1), add 10g of xylene to dilute it, and transfer it to a stainless steel reactor that has been dried in advance, and replace the atmosphere in the reactor with nitrogen and hydrogen three times in sequence. Inject 1g of the hydrogenation catalyst prepared above into the reactor, pressurize it to 4MPa with hydrogen, start stirring and heat to 80°C. After 4 hours of reaction, the double bond content in the product is reduced to 1%, which is the end point of the hydrogenation reaction, and the corresponding hydrogenated polymer solution is obtained. After cooling, the reaction solution is poured into acidified ethanol, flocculated and washed three times, and the precipitated polymer is washed three times with deionized water and dried in a vacuum oven. The obtained hydrogenated polymer, i.e., polymer (HPM-3), has a weight-average molecular weight Mw of 1.1×10 4 , the residual double bonds are less than 1%.
[0149] (3-3) Preparation of hydrogenated polymer membrane
[0150] Take 2 g of the hydrogenated polymer obtained in step (3-2) and add 10 ml of xylene to dissolve it. Pour the dissolved polymer solution into a clean mold and evaporate the solvent to obtain the corresponding hydrogenated polymer film.
[0151] The glass transition temperature (Tg), stress birefringence (CR), refractive index (nd) and Abbe number (νd) of the hydrogenated polymer HPM-3 obtained by the above method are shown in Table 1.
[0152] Example 4
[0153] HPM-4 Preparation
[0154]
[0155] (4-1) Preparation of Ring-Opening Polymer (PM-4)
[0156] In a glove box, take 0.19g of norbornene, 0.32g of tetracyclododecene, and 9.30g of monomer M-4, dissolve them in 32g of xylene, and then add 16.8mg of 1-hexene. Add the above solution to a 250ml flask equipped with a magnet, start stirring and heating; when the temperature rises to 40°C, add 0.3mg of Grubbs second-generation catalyst to the flask to start polymerization. After 30min of polymerization, add 1g of ethanol to terminate the active center. The total amount of the reaction solution is 40g. The weight average molecular weight Mw of the obtained ring-opening polymer is 5.4×10 4 , the conversion rate of monomer to polymer is >99%.
[0157] (4-2) Hydrogenation of Ring-Opening Polymer (HPM-4)
[0158] In a glove box, 25.8 μmol (100 μmol) of nickel acetylacetonate was weighed and dispersed in 5 g of xylene. 0.4 g (0.5 mmol) of triisobutylaluminum was extracted and injected into the nickel acetylacetonate. The mixture was reacted for 2 min to prepare a hydrogenation catalyst.
[0159] Weigh 20g of the ring-opening polymer reaction liquid in (4-1), add 20g of xylene to dilute it, and transfer it to a stainless steel reactor that has been dried in advance, and replace the atmosphere in the reactor with nitrogen and hydrogen three times in sequence. Inject 2g of the hydrogenation catalyst prepared above into the reactor, pressurize it to 4MPa with hydrogen, start stirring and heat to 80°C. After 4 hours of reaction, the double bond content in the product is reduced to 1%, which is the end point of the hydrogenation reaction, and the corresponding hydrogenated polymer solution is obtained. After cooling, the reaction solution is poured into acidified ethanol, flocculated and washed three times, and the precipitated polymer is washed three times with deionized water and dried in a vacuum oven. The obtained hydrogenated polymer, i.e., polymer (HPM-4), has a weight-average molecular weight Mw of 5.5×10 4 , the residual double bonds are less than 1%.
[0160] (4-3) Preparation of hydrogenated polymer membrane
[0161] Take 2 g of the hydrogenated polymer obtained in step (4-2) and add 10 ml of xylene to dissolve it. Pour the dissolved polymer solution into a clean mold and evaporate the solvent to obtain the corresponding hydrogenated polymer film.
[0162] Table 1 shows the glass transition temperature (Tg), stress birefringence (CR), refractive index (nd) and Abbe number (νd) of the hydrogenated polymer HPM-4 obtained by the above method.
[0163] Example 5
[0164] HPM-5 preparation
[0165]
[0166] (5-1) Preparation of Ring-Opening Polymer (PM-5)
[0167] In a glove box, take 2.11g of dicyclopentadiene, 2.24g of tetracyclododecene, and 2.51g of monomer M-5, dissolve them in 33g of cyclohexane, and then add 16.8mg of 1-hexene. Add the above solution to a 250ml flask equipped with a magnetic, start stirring and heating; when the temperature rises to 40°C, add 0.3mg (4μmol) of Grubbs second-generation catalyst to the flask to start polymerization. After 30min of polymerization, add 1g of ethanol to terminate the active center. The total amount of the reaction solution is 40g. The weight average molecular weight Mw of the obtained ring-opening polymer is 4.3×10 4 , the conversion rate of monomer to polymer is >99%.
[0168] (5-2) Hydrogenation of Ring-Opening Polymer (HPM-5)
[0169] In a glove box, 25.8 μmol (100 μmol) of nickel acetylacetonate was weighed and dispersed in 5 g of decahydronaphthalene. 0.4 g (0.5 mmol) of triisobutylaluminum was extracted and injected into the nickel acetylacetonate. The mixture was reacted for 2 min to prepare a hydrogenation catalyst.
[0170] Weigh 20g of the ring-opening polymer reaction liquid in (5-1), add 20g of cyclohexane to dilute it, and transfer it to a stainless steel reactor that has been dried in advance, and replace the atmosphere in the reactor with nitrogen and hydrogen three times in sequence. Inject 2g of the hydrogenation catalyst prepared above into the reactor, pressurize it to 4MPa with hydrogen, start stirring and heat to 80°C. After 4 hours of reaction, the double bond content in the product is reduced to 1%, which is the end point of the hydrogenation reaction, and the corresponding hydrogenated polymer solution is obtained. After cooling, the reaction solution is poured into acidified ethanol, flocculated and washed three times, and the precipitated polymer is washed three times with deionized water and dried in a vacuum oven. The obtained hydrogenated polymer, i.e., polymer (HPM-5), has a weight-average molecular weight Mw of 4.5×10 4 , the residual double bonds are less than 1%.
[0171] (5-3) Preparation of hydrogenated polymer membrane
[0172] Take 2 g of the hydrogenated polymer obtained in step (5-2) and add 10 ml of xylene to dissolve it. Pour the dissolved polymer solution into a clean mold and evaporate the solvent to obtain the corresponding hydrogenated polymer film.
[0173] Table 1 shows the glass transition temperature (Tg), stress birefringence (CR), refractive index (nd) and Abbe number (νd) of the hydrogenated polymer HPM-5 obtained by the above method.
[0174] Example 6
[0175] HPM-6 Preparation
[0176]
[0177] (6-1) Preparation of Ring-Opening Polymer (PM-5)
[0178] In a glove box, take 2.64g of dicyclopentadiene, 2.56g of tetracyclododecene, and 1.13g of monomer M-6, dissolve them in 53g of cyclohexane, and then add 1.8mg of 1-hexene. Add the above solution to a 250ml flask equipped with a magnetic, start stirring and heating; when the temperature rises to 40°C, add 0.3mg (4μmol) of Grubbs second-generation catalyst to the flask to start polymerization. After 30min of polymerization, add 1g of ethanol to terminate the active center. The total amount of the reaction solution is 60g. The weight average molecular weight Mw of the obtained ring-opening polymer is 41.8×10 4 , the conversion rate of monomer to polymer is >99%.
[0179] (6-2) Hydrogenation of Ring-Opening Polymer (HPM-5)
[0180] In a glove box, 25.8 μmol (100 μmol) of nickel acetylacetonate was weighed and dispersed in 5 g of decahydronaphthalene. 0.4 g (0.5 mmol) of triisobutylaluminum was extracted and injected into the nickel acetylacetonate. The mixture was reacted for 2 min to prepare a hydrogenation catalyst.
[0181] Weigh 20g of the ring-opening polymer reaction liquid in (6-1), add 20g of cyclohexane to dilute it, and transfer it to a stainless steel reactor that has been dried in advance, and replace the atmosphere in the reactor with nitrogen and hydrogen three times in sequence. Inject 2g of the hydrogenation catalyst prepared above into the reactor, pressurize it to 4MPa with hydrogen, start stirring and heat to 80°C. After 4 hours of reaction, the double bond content in the product is reduced to 1%, which is the end point of the hydrogenation reaction, and the corresponding hydrogenated polymer solution is obtained. After cooling, the reaction solution is poured into acidified ethanol, flocculated and washed three times, and the precipitated polymer is washed three times with deionized water and dried in a vacuum oven. The obtained hydrogenated polymer, i.e., polymer (HPM-6), has a weight-average molecular weight Mw of 45.8×10 4 , the residual double bonds are less than 1%.
[0182] (6-3) Preparation of hydrogenated polymer membrane
[0183] Take 2 g of the hydrogenated polymer obtained in step (6-2) and add 10 ml of xylene to dissolve it. Pour the dissolved polymer solution into a clean mold and evaporate the solvent to obtain the corresponding hydrogenated polymer film.
[0184] Table 1 shows the glass transition temperature (Tg), stress birefringence (CR), refractive index (nd) and Abbe number (νd) of the hydrogenated polymer HPM-6 obtained by the above method.
[0185] Example 7
[0186] HPM-7 preparation
[0187]
[0188] (7-1) Preparation of Ring-Opening Polymer (PM-7)
[0189] In a glove box, take 2.64g of dicyclopentadiene, 2.89g of tetracyclododecene, and 0.59g of monomer M-7, dissolve them in 30g of cyclohexane, and then add 57.1mg of 1-hexene. Add the above solution to a 250ml flask equipped with a magnetic, start stirring and heating; when the temperature rises to 40°C, add 0.3mg (4μmol) of Grubbs second-generation catalyst to the flask to start polymerization. After 30min of polymerization, add 1g of ethanol to terminate the active center. The total amount of the reaction solution is 40g. The weight average molecular weight Mw of the obtained ring-opening polymer is 1.3×10 4 , the conversion rate of monomer to polymer is >99%.
[0190] (7-2) Hydrogenation of Ring-Opening Polymer (HPM-7)
[0191] In a glove box, 25.8 μmol (100 μmol) of nickel acetylacetonate was weighed and dispersed in 5 g of decahydronaphthalene. 0.4 g (0.5 mmol) of triisobutylaluminum was extracted and injected into the nickel acetylacetonate. The mixture was reacted for 2 min to prepare a hydrogenation catalyst.
[0192] Weigh 20g of the ring-opening polymer reaction liquid in (5-1), add 20g of cyclohexane to dilute it, and transfer it to a stainless steel reactor that has been dried in advance, and replace the atmosphere in the reactor with nitrogen and hydrogen three times in sequence. Inject 2g of the hydrogenation catalyst prepared above into the reactor, pressurize it to 4MPa with hydrogen, start stirring and heat to 80°C. After 4 hours of reaction, the double bond content in the product is reduced to 1%, which is the end point of the hydrogenation reaction, and the corresponding hydrogenated polymer solution is obtained. After cooling, the reaction solution is poured into acidified ethanol, flocculated and washed three times, and the precipitated polymer is washed three times with deionized water and dried in a vacuum oven. The obtained hydrogenated polymer, i.e., polymer (HPM-7), has a weight-average molecular weight Mw of 1.5×10 4 , the residual double bond content is <1%.
[0193] (7-3) Preparation of hydrogenated polymer membrane
[0194] Take 2 g of the hydrogenated polymer obtained in step (7-2) and add 10 ml of xylene to dissolve it. Pour the dissolved polymer solution into a clean mold and evaporate the solvent to obtain the corresponding hydrogenated polymer film.
[0195] Table 1 shows the glass transition temperature (Tg), stress birefringence (CR), refractive index (nd) and Abbe number (νd) of the hydrogenated polymer HPM-7 obtained by the above method.
[0196] Comparative Example 1
[0197] The preparation method was prepared by referring to Example 1, except that the monomer M-1 was replaced by an equal amount of norbornene, and other operations and parameters remained unchanged to obtain a polymer. The performance test results are shown in Table 1.
[0198] Comparative Example 2
[0199] The preparation method of Example 3 was used with the exception that the monomer M-3 was replaced by an equal amount of norbornene, and other operations and parameters remained unchanged to obtain a polymer. The performance test results are shown in Table 1.
[0200] Comparative Example 3
[0201] The preparation method of Example 5 was used with the exception that the monomer M-5 was replaced by an equal amount of dicyclopentadiene, and other operations and parameters remained unchanged to obtain a polymer. The performance test results are shown in Table 1.
[0202] In addition, the performance of three brands of cycloolefin polymers, namely, ZEONEX K26R and ZEONEX 690R of ZEON Company and ARTON F4520 of JSR Company, which are the mainstream commercial products on the market, were also measured under the same conditions. The results are shown in Table 1.
[0203] Table 1 Physical properties of polymers prepared in the examples of the present invention and comparative examples and properties of commercially available cycloolefin polymers
[0204]
[0205] Compared with the mainstream grades and comparative examples of commercial cycloolefin polymers, the birefringence of the cycloolefin polymer provided by the present invention is significantly reduced, the glass transition temperature and the heat deformation temperature are significantly increased, and the refractive index, high Abbe's property and low hygroscopicity are taken into consideration at the same time. According to the present invention, a composition that can be advantageously used as a material for an optical element, etc., and a molded body that can be advantageously used as an optical element, etc. are provided.
Claims
1. A low birefringence, high heat resistance cycloolefin polymer, characterized in that: Contains the structural unit shown in the following formula I: In formula I, R is a cycloalkyl group, preferably one or more selected from cyclopentanyl, cyclohexanyl, cycloheptyl, cyclooctyl, norbornyl, adamantyl and substituted structures thereof; R1, R2, R3, and R4 are independently selected from one or more selected from H, methyl, ethyl, butyl, hexyl, cyclohexyl, and phenyl; R1 and R4 are bonded to each other to form a ring or are not bonded; L is -CH2-CH2- or -CH=CH-; and n is an integer from 0 to 2.
2. The low birefringence, high heat resistance cyclic olefin polymer according to claim 1, characterized in that: Contains the structural unit shown in the following formula II: In Formula II, RC is any one of an alkyl group and a cycloalkyl group, preferably a C4-C8 alkyl group, a C5-C 15 Any of the cycloalkyl groups of C4-C8, more preferably C4-C8 alkylene groups, C5-C 15 Any one of the cyclopentane-containing structural groups.
3. The low birefringence, high heat-resistant cyclic olefin polymer according to claim 2, characterized in that: Taking the total molar amount of the structural unit represented by formula I and the structural unit represented by formula II as 100%, the molar content of the structural unit represented by formula I is 5-100 mol%, and the molar content of the structural unit represented by formula II is 0-95 mol%.
4. The low birefringence, high heat resistance cyclic olefin polymer according to claim 1, characterized in that: The structural unit shown in formula I is prepared from the compound shown in formula I-A: In Formula Ⅰ-A, R, R1, R2, R3, and n are defined the same as R, R1, R2, R3, and n in Formula Ⅰ above; Preferably, the compound represented by formula Ⅰ-A is selected from at least one of compounds M-1, M-2, M-3, M-4, M-5, M-6, and M-7 having the following structures:
5. The low birefringence, high heat resistance cyclic olefin polymer according to claim 2, characterized in that: The structural unit shown in formula II is prepared by the cycloolefin compound shown in formula II-A: Wherein, the definition of RC is the same as that of RC in the above formula II; Preferably, the cycloolefin compound represented by formula II-A is at least one selected from cyclopentene, cyclohexene, cycloheptene, cyclooctene, cyclooctadiene, norbornene, dicyclopentadiene and tetracyclododecene.
6. The low birefringence, high heat-resistant cyclic olefin polymer according to any one of claims 1 to 5, characterized in that: The number average molecular weight is 5000-100000; and / or the double bond molar content is ≤50%, preferably ≤1%.
7. A method for preparing a low birefringence, high heat-resistant cycloolefin polymer according to any one of claims 1 to 6, characterized in that the steps include: (1) Polymerization: mixing the compound represented by formula Ⅰ-A with the cycloolefin compound represented by formula Ⅱ-A and a chain transfer agent to carry out polymerization reaction to obtain a polymer intermediate; (2) Hydrogenation: The polymer intermediate obtained in step (1) is subjected to a hydrogenation reaction with hydrogen to obtain the low birefringence and high heat resistance cycloolefin polymer.
8. The preparation method according to claim 7, characterized in that: The polymerization process of step (1) is specifically as follows: adding the compound represented by formula Ⅰ-A, the optional cycloolefin compound represented by formula Ⅱ-A, a chain transfer agent, and a ring-opening metathesis polymerization catalyst into a solvent to carry out a solution polymerization reaction; Preferably, the molar ratio of the compound represented by formula Ⅰ-A to the optional cycloolefin compound represented by formula Ⅱ-A is (5-100): (95-0); Preferably, the chain transfer agent is selected from at least one of olefin compounds containing terminal double bonds, preferably at least one of 1-pentene, 1-hexene, 1-heptene, 1-octene, styrene, and vinyl ether; Preferably, the molar ratio of the chain transfer agent to the sum of the compound represented by formula Ⅰ-A and the optional cycloolefin compound represented by formula Ⅱ-A is 1:(50-2000).
9. The preparation method according to claim 7 or 8, characterized in that: The ring-opening metathesis polymerization catalyst is any one of a multi-component tungsten catalyst, a Grubbs series catalyst, and a Schrock series catalyst, or a combination of at least two of them, preferably a Grubbs series catalyst; Preferably, the mass ratio of the ring-opening metathesis polymerization catalyst to the sum of the compound represented by formula Ⅰ-A and the optional cycloolefin compound represented by formula Ⅱ-A is 1:10000 to 1000000; Preferably, the solvent is selected from at least one of aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, halogenated aromatic hydrocarbon solvents, and ether solvents; Preferably, the aliphatic hydrocarbon solvent is selected from at least one of n-hexane and heptane; Preferably, the alicyclic hydrocarbon solvent is selected from at least one of cyclopentane, cyclohexane, methylcyclohexane and dimethylcyclohexane; Preferably, the aromatic hydrocarbon solvent is selected from at least one of benzene, toluene and xylene; Preferably, the halogenated aromatic hydrocarbon solvent is selected from at least one of chlorobenzene and dichlorobenzene; Preferably, the ether solvent is selected from at least one of diethyl ether and tetrahydrofuran; Preferably, the total mass of the compound represented by formula Ⅰ-A and the optional cycloolefin compound represented by formula Ⅱ-A accounts for 5 to 70% of the mass of the solvent, preferably 5 to 50%; Preferably, the solution polymerization reaction is carried out at a temperature of 0 to 200° C., preferably 50 to 150° C., and a time of 1 to 60 min, preferably 1 to 30 min.
10. The preparation method according to claim 7, characterized in that: The hydrogenation process of step (2) is specifically as follows: the polymer intermediate obtained in step (1) is subjected to a hydrogenation reaction with hydrogen in the presence of a hydrogenation catalyst; Preferably, the hydrogenation catalyst comprises a homogeneous or heterogeneous catalyst; More preferably, the heterogeneous catalyst is selected from at least one of metal-supported silica, metal-supported alumina, metal-supported titanium oxide, skeleton nickel, and palladium-carbon catalyst; wherein the metal is selected from at least one of nickel, palladium, platinum, rhodium, and ruthenium; preferably, the amount of the heterogeneous catalyst added is 0.5 to 10% of the mass of the polymer intermediate solution obtained in step (1); More preferably, the homogeneous catalyst is selected from at least one of soluble complexes of nickel, titanium, palladium, platinum, rhodium and ruthenium metals; preferably, the amount of the homogeneous catalyst added is 0.001 to 10% of the mass of the polymer intermediate solution obtained in step (1); Preferably, the hydrogenation reaction has a hydrogenation temperature of 80-200° C. The amount of hydrogen fed is determined by the charging pressure, and the charging pressure of hydrogen is controlled to be 1-7 MPa.
Citation Information
Patent Citations
Cycloolefin copolymer as well as preparation method and application thereof
CN116675809A
Phenylfluorene type cycloolefin addition polymer and preparation method thereof
CN117801166A
Phenylfluorene type cycloolefin polymer and preparation method thereof
CN117801228A
Cyclic olefin polymer, method for producing same, and optical element
WO2021107041A1